A Critical Interpretation on Pandu Vyadhi (Iron deficiency anemia): A Brief Review - Chandeshwar, Sonal; Khichariya, S D; Baghel, Pramod Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Pandu denotes Paleness in the body is predominant throughout this condition. It may be co-related with current disease anaemia because of its resemblance. Nearly all of our Acharyas will clarify Pandu. Rasavaha and Raktavaha srotas (channels carrying lymph/plasma and blood) were primarily involved in the pathogenesis of Pandu through Ahara (diet) and Vihar(lifestyle) . The evolving lifestyle of humans plays a major role in the manifestation of various diseases. One of them is Pandu as well. Ama, which further activates Agnimandya (weak digestion) and eventually Amayukta Ahara Rasa,(undigested food juice) is formed by our flawed eating habits and lifestyle. It hampers Rasa Dhatu Utpatti, and Pandu(Anemia) manifests itself. As a result of the Rakta depletion,(blood deficiency) Aggravated Pitta is responsible for generating Posaka (nutrient portion) from the Rasadhatu.(Plasma) Pandu, (Iron Deficiency Anaemia.)